2022
DOI: 10.1093/mnras/stac3567
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between photoionized and collisionally ionized gas in the circumgalactic medium

Abstract: Most studies of highly ionized plasmas have historically assumed ions are either in photoionization equilibrium, PIE, or collisional ionization equilibrium, CIE, sometimes including multiple phases with different relevant mechanisms. Simulation analysis packages, on the other hand, tend to use precomputed ion fraction tables which include both mechanisms, among others. Focusing on the low-density, high temperature phase space likely to be most relevant in the circumgalactic medium, in this work we show that mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In these conditions O vii is mainly produced via collisional ionisation (e.g. Strawn et al 2023). The demonstration that the oxygen density also peaks in these regions (see Sect.…”
Section: Thermodynamic Large-scale Structurementioning
confidence: 93%
See 1 more Smart Citation
“…In these conditions O vii is mainly produced via collisional ionisation (e.g. Strawn et al 2023). The demonstration that the oxygen density also peaks in these regions (see Sect.…”
Section: Thermodynamic Large-scale Structurementioning
confidence: 93%
“…Towards lower densities, the UV background photon density per particle increases and thus a larger fraction of O vii is produced via photoionisation (e.g. Nelson et al 2018;Wijers et al 2019;Strawn et al 2023). However, only the high-energy tail of the UV background photons exceeds the ionisation energy of O vii (Haardt & Madau 2001), and therefore this effect does not compensate for the inefficiency of CIE in the production of O vii.…”
Section: Thermodynamic Large-scale Structurementioning
confidence: 99%
“…Each phaseplot is repeated four times vertically, and plotted over each are the 1% and 20% ion fraction contours for the four ions being analyzed in this work. As argued in Strawn et al (2021) and Strawn et al (2023a), in the horizontal "upper" ridge, each ion should be considered collisionally ionized (CI), and in the diagonal "lower" ridge, it should be considered photoionized (PI). 53 The data in Galbiati et al (2023) are generally reported as equivalent widths rather than column densities.…”
Section: Comparison With Observationsmentioning
confidence: 99%